Carbon sequestration and mechanisms of soil organic matter stabilization in Technosols constructed for mine reclamation - Ruiz, Francisco (2023)
Human impact on the climate represents a global crisis. Although essential for economic growth, mining contributes to this scenario by completely removing soil and vegetation and generating large-scale waste, which exacerbates greenhouse gas emissions. In this context, the present thesis explores the importance of Technosols (i.e., soils developed from anthropogenic materials such as urban, industrial, and mining waste) in the reclamation of mining areas as a strategy to mitigate carbon emissions from mining. Through a combination of methods, including spectroscopic techniques (FTIR and XPS), thermal analyses (TG-DSC, Rock-Eval, Pyrolysis-GC/MS), and wet chemical extraction methods, the mechanisms responsible for stabilizing soil organic matter (SOM) were thoroughly investigated. Furthermore, using georeferenced data and information on carbon stocks, the potential for carbon sequestration in Technosols across the entire Brazilian territory was estimated. To understand the processes governing the accumulation of SOM during the initial stages of Technosol development, a successful case of mining area reclamation was used as a model, involving the combination of limestone waste and tropical grasses. It was shown that the rapid weathering of mining waste resulted in the formation of reactive secondary minerals, such as montmorillonite and poorly crystalline iron oxides, favoring the development of interactions between organic and mineral phases, as well as the formation of stable soil aggregates. In turn, SOM accumulated both in the form of mineral-associated organic matter (MAOM) and particulate organic matter (POM). The formation of cation bridges between organic compounds and mineral surfaces, mediated by calcium (Ca) and magnesium (Mg), along with the kerogen present in the waste, ensured high thermal and biological stability of SOM, surpassing that of a natural soil used as reference. The significant accumulation of SOM was responsible for transforming limestone mining waste into fertile soils suitable for agriculture in only 20 years. At the national level, it was estimated that the reclamation of mining areas through the construction of Technosols has the potential to reduce carbon dioxide emissions resulting from soil loss by up to 60%. In addition to carbon sequestration, Technosols demonstrate great potential for restoring ecosystem services provided by soil, such as nutrient cycling, water cycle regulation, and biodiversity conservation. The use of Technosols in the reclamation of mining-degraded areas emerges as a promising strategy not only for Brazil but also for other countries with extensive mining areas. Future work should explore the wide variety of available waste materials, including those from mining, urban, and industrial sources, in order to create soils with high potential for carbon sequestration and ecosystem services provision.